Denture Adhesive Utilization and Associated Factors among Dental Practitioners in the Eastern Province, Saudi Arabia - Mohammed M. Gad; Mayyasah O. Almusallam; Fadak H. Almarar; Haya O. Al khaldi; Alhanoof K. Aldossary; Wejdan M. Almutairi; Nawaf A. Alghamdi; Yasser S. Alssaialiy; Nawaf I. Alghamdi; Muhammad A. Nazir (Medicina, 2023)
Background: Denture adhesives (DAs) enhance denture retention and stability, thus improving functions of removable prostheses. However, the adverse effects of DAs on denture foundation area were also reported. The clinical use of DAs among dentists has not been investigated in Saudi Arabia. Therefore, this study aimed to evaluate utilization of DAs and associated factors among dental practitioners in Saudi Arabia. Methods: This cross-sectional study included dental professionals practicing in both public and private sectors in the Eastern Province of Saudi Arabia. A self-administered pilot tested questionnaire was distributed among participants. The questionnaire has questions related to demographic information, knowledge and awareness, and the utilization of DAs. Bivariate and multiple logistic regression analyses were performed. Results: The study included 279 participants with a response rate of 79.03%. The majority of participants (61.6%) were below 35 years of age, males (56.6%), general dentists (57.3%), and worked in the private sector (59.9%). Less than half of the participants (39.4%) used DAs in their dental practice, and 64.5% recommended using DAs when needed. The most reported complications of DAs included inflammation (58.40%), ulcers (35.10%), and whitish color (31.20%) of denture foundation area. A vast majority (83.90%) reported that DAs improve retention of the dentures. About 55.2% of the participants were taught about DAs in their undergraduate programs, 12.5% attended continuing education, and 21.5% updated their knowledge about DAs. Multiple logistic regression showed that those who attended continuing education activities (adjusted OR = 2.41, p = 0.036) and updated their knowledge about DAs (adjusted OR = 4.43, p = < 0.001) were significantly more likely to use DAs in their dental practice. Conclusion: A minority of dental practitioners used DAs in their practices. Attending continuing education programs and updating knowledge of DAs were significantly associated with DAs utilization.